Retrospective estimation of the course of the postoperative period among patients treated with surgery because of the endometrial carcinoma depending on the value of the BMI ratio making allowances for co-existing diseases - Górski, Jarosław; Szyłło, Krzysztof; Kamer-Bartosińska, Anna (Menopause Review/Przegląd Menopauzalny, 2005)
Endometrial carcinoma is fifth in the frequency of occuring cancer among women. Approximately 75% of all ill women are in their postmenopausal period. Women with endometrial carcinoma are characterised by more frequent co-existence of additional diseases such as: obesity, diabetes, hypertensio arterialis. In Europe 5% which is 70 000 newly diagnosed cancers are relevant to overweight. Among them the most often is endometrial carcinoma. The aim of this study is an retrospective estimation of the course of the postoperative period among patients treated with surgery because of the endometrial carcinoma depending on the value of the BMI ratio making allowances for co-existing diseases. Estimating the course of postoperative period following subjects have been taken under consideration: the duration of hospitalisation, the manner of vulnus healing, presence or lack of hematoma in the postoperational vulnus, body temperature ł38oC. In conducted analysis co-existing diseases have been taken under consideration: diabetes mellitus, hypertensio arterialis, ischaemic heart disease and theirs influence on the process of postoperative period.